PENGARUH PENGGUNAAN MODEL DISCOVERY LEARNING BERBANTUAN MEDIA OBJEK LANGSUNG TERHADAP KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VII SMP NEGERI 2 PADANG - Ruspayanti, Risya; Gani, Erizal; Noveria, Ena (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
The purpose of this study is to (1) desciribe the skill of writing the news berfore using modeldiscovery learningmedia assisted object directly, (2) desciribe the skill of writing the news aftermodeldiscovery learningmedia assisted object directly, (3) describe effect between using of modeldiscovery learningmedia assisted object directlyon the skill of writing to the news of class VII SMPNegeri 2 Padamg. The data in this research is the score of writing skill of the news. The source of this research data of class VII of SMPNegeri 2 Padang, amounting to 32 people.The findings of this research it is concluded that there is a significant effect between using of modeldiscovery learningmedia assisted object directlyon the skill of writing to the news of class VII of SMPNegeri 2 Padang.Â Kata kunci: Â pengaruh, model pembelajaran kooperatf tipe think pair share, dan keterampilan menulis berita.